PAIN LEVEL IN PATIENTS WITH CANCER UNDERGOING INPATIENT TREATMENTS AT TRA VINH GENERAL HOSPITAL - Nguyen, Thi Ngoan; Nguyen, Le Thanh Truc; Tran, Thi Kim Chi (Cantho Journal of Medicine and Pharmacy, 2023)
Background: Cancer (K) is a major burden of disease and the leading cause of death worldwide, and accounting for nearly 10 million deaths in 2020. Therefore, there have been many studies on drugs and treatment regimens to cure or treat cancer. In addition, pain is a common symptom amongst patients with cancer. Adequate pain assessments to develop appropriate care plans and treatment strategies is critical to reduce its symptoms, improve the quality of life and health outcomes in this population. Objectives: To determine the pain level and factors affecting proper management in cancer patients undergoing in-patient treatment at Tra Vinh General Hospital. Materials and methods: The descriptive cross-sectional method and carrying out direct interviews on 110 patients diagnosed with cancer, from December 2020 to June 2021 at Tra Vinh General Hospital. Results: the male and female ratio was nearly equal, accounting for 0.96 and 1, respectively, the average age was 61.1 and the Kinh ethnic group accounted for 63%. In regarding to the numerical rating scale (NRS), 100% of the patients had pain, in which the majority of patients fell into the moderate-to-severe category (38.2% and 34.5%, respectively). There was a relationship between pain level and pain locations with p=0.0005; and between pain level and pain type with p=0.001. Conclusion: All participant patients affected by cancer reported pain, and more than half of them experienced pain of moderate-to-severe intensity. In addition, the study showed the significant correlation among pain level with pain locations, pain patterns and appetite decrease (p<0.05).